Lending-of-last-resort is as lending-of-last-resort does: Central bank liquidity provision and interbank market functioning in the euro area - Garcia-de-Andoain, Carlos; Heider, Florian; Hoerova, Marie; Manganelli, Simone (Journal of Financial Intermediation, 2016)
This paper investigates the impact of ample liquidity provision by the European Central Bank on the functioning of the overnight unsecured interbank market from 2008 to 2014. We use novel data on interbank transactions derived from TARGET2, the main euro area payment system. To identify exogenous shocks to central bank liquidity, we exploit the timing of ECB liquidity operations and use a simple structural vector auto-regression framework. We argue that the ECB acted as a de facto lender-of-last-resort to the euro area banking system and identify two main effects of central bank liquidity provision on interbank markets. First, central bank liquidity replaces the demand for liquidity in the interbank market, especially during the financial crisis (2008–2010). Second, it increases the supply of liquidity in the interbank market in stressed countries (Greece, Italy and Spain) during the sovereign debt crisis (2011–2013).